Repurposing MS immunotherapies for CIDP and other autoimmune neuropathies: unfulfilled promise or efficient strategy? - Felix Kohle; Marinos C. Dalakas; Helmar C. Lehmann (Therapeutic Advances in Neurological Disorders, 2023)
Despite advances in the treatment of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and other common autoimmune neuropathies (AN), still-many patients with these diseases do not respond satisfactorily to the available treatments. Repurposing of disease-modifying therapies (DMTs) from other autoimmune conditions, particularly multiple sclerosis (MS) and neuromyelitis optica spectrum disorders (NMOSD), is a promising strategy that may accelerate the establishment of novel treatment choices for AN. This approach appears attractive due to homologies in the pathogenesis of these diseases and the extensive post-marketing experience that has been gathered from treating MS and NMOSD patients. The idea is also strengthened by a number of studies that explored the efficacy of DMTs in animal models of AN but also in some CIDP patients. We here review the available preclinical and clinical data of approved MS therapeutics in terms of their applicability to AN, especially CIDP. Promising therapeutic approaches appear to be B cell–directed and complement-targeting strategies, such as anti-CD20/anti-CD19 agents, Bruton’s tyrosine kinase inhibitors and anti-C5 agents, as they exert their effects in the periphery. This is a major advantage because, in contrast to MS, their action in the periphery is sufficient to exert significant immunomodulation.